2008
DOI: 10.1139/w07-117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Streptococcus pneumoniae genes specifically induced in mouse lung tissues

Abstract: To identify Streptococcus pneumoniae genes expressed specifically during infections, a selection system based on the in vivo expression technology (IVET) was established. galU, which is critical for capsular polysaccharide biosynthesis, and lacZY encoding beta-galactosidase were employed as dual reporter genes to screen in-vivo-induced (ivi) genes of S. pneumoniae. The galU-deficient mutant of S. pneumoniae is incapable of utilizing galactose, thus failing to synthesize capsular polysaccharide, and therefore l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…rafX (accession no. AE007480) was identified as an in vivo-inducible gene in a model of murine pneumonia and sepsis in our laboratory (38). rafX is part of the raf operon with five upstream genes that have been shown to be involved in raffinose metabolism; nevertheless, the role of the RafX protein has not been elucidated (39).…”
Section: Resultsmentioning
confidence: 99%
“…rafX (accession no. AE007480) was identified as an in vivo-inducible gene in a model of murine pneumonia and sepsis in our laboratory (38). rafX is part of the raf operon with five upstream genes that have been shown to be involved in raffinose metabolism; nevertheless, the role of the RafX protein has not been elucidated (39).…”
Section: Resultsmentioning
confidence: 99%
“…A previous report demonstrated that expression of the operon containing ugl and spr0293 to spr0295 is upregulated during infection of the lung, indicating that utilization of hyaluronic acid may also contribute to bacterial growth during disease (33). It has been suggested that the pneumococcal hyaluronate lyase aids bacterial invasion, and it is possible that localized invasion contributes to bacterial colonization in addition to degrading hyaluronic acid for nutrition (22,47).…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been employed to screen in vivo-induced genes, including in vivo expression technology (IVET) (12), signature-tagged mutagenesis (STM) (13,14), differential fluorescence induction (DFI) (15)(16)(17), DNA microarray (18,19), reverse vaccinology (20,21), antigenome technology (22,23), and genomic array footprinting (GAF) (24). The availability of complete pathogen genome sequences has stimulated the development and wide-spread application of DNA arrays, which has revolutionized the study of genes that are involved in microbial pathogenesis (25).…”
Section: Introductionmentioning
confidence: 99%